Auditoría de la seguridad informática a la empresa radio Machala de la ciudad de Machala. - Torres Paltan, Jessica Catalina (My University, 2019)
The communication is an indispensable social function, it allows to inform, to make known eventualities, news and to express its opinion in public form; One of the media that has most stood out over the years is the radio because of its scope, ease of tuning, variety in programming, simplicity and integration as part of the national culture. A literature review is applied, holistically focused in an exploratory way; with the aim of combining the theoretical-practical criteria related to business sciences by identifying, analyzing and solving problems in institutions or corporate entities. Auditing is an essential process in any company, especially those that manage technological resources through networks and the internet; this refers to the need to harmonize their potentialities and benefits; the present study relates the analysis made to RADIO MACHALA auditing its computer systems; with the purpose of identifying their vulnerabilities while at the same time establishing controls to guarantee the security of their assets.
La comunicación es una función social indispensable, permite informar, dar a conocer eventualidades, noticias y expresar su opinión en forma pública; uno de los medios que más ha destacado a lo largo de los años es la radio debido a su alcance, facilidad de sintonizar, variedad en programación, simplicidad e integración como parte de la cultura nacional. Se aplica una revisión bibliográfica, enfocada holísticamente en forma exploratoria; con el afán de conjugar los criterios teóricos-prácticos afines a ciencias empresariales al identificar, analizar y solventar problemas en las instituciones o entidades corporativas. La auditoría es un proceso esencial en toda empresa, en especial en aquellas que gestionan recursos tecnológicos mediante redes e internet; esto hace alusión a la necesidad de armonizar sus potencialidades y bondades; el presente estudio relata el análisis realizado a RADIO MACHALA auditando sus sistemas informáticos; con la finalidad de identificar sus vulnerabilidades, a la vez que se plantean controles para garantizar la seguridad de sus activos.
Keywords: AUDITORÍA INFORMÁTICA; RADIODIFUSIÓN; VULNERABILIDADES; TIC`S